COMPARATIVE STUDY OF THE PROCESS OF OBTAINING ALGINIC ACID IN BROWN ALGAE (SEA): Macrocystis pyrifera and Lessonia trabeculata. - Caja R., Víctor R. (2005)
The purpose of this research is to evaluate the performance of production of alginic acid laboratory scale in order to compare the results of the kinds of brown algae: Lessonia trabeculata vs. Macrocystis pyrifera. The results indicate higher performance in the production of acid alginic from Macrocystis pyrifera regarding Lessonia trabeculata.